Identifying coping strategies used by patients at a transgender health clinic through analysis of free‐text autobiographical narratives. (24th February 2021) - Zottola, Angela; Jones, Lucy; Pilnick, Alison; Mullany, Louise; Pierre Bouman, Walter; Arcelus, Jon
Abstract: Background: This paper presents an analysis of 32 narratives written by patients waiting for assessment at a transgender health clinic (THC) in England. Narratives are autobiographical free texts, designed to allow patients to describe in their own words their experiences of their gender identity and/or transition prior to a clinic appointment, as part of the assessment process. Objective: Narratives were analysed to identify actions prospective patients had taken to manage their (usually lengthy) waiting times, so that these 'coping strategies' could be shared with future patients. Design: Corpus linguistic methodology was utilized to identify common patterns across the whole corpus of text‐based data, augmented with more detailed sociolinguistic analysis of individual narratives. Results: There are broad commonalities in the way the transition experience is described across the corpus in terms of presentation of key experiences and feelings. There are specific descriptions of a number of recurring coping strategies, both positive and negative. Conclusion: The empowerment value of writing these narratives may be limited; the existence of recurring key features suggests that patients may feel they have to present their experiences in certain ways to be accepted for treatment. However, dissemination of some positive coping strategies may help future clients of THCs to better cope with waiting times, as well as assisting practitioners in THCs in supporting their patients during this wait. Patient/Public Contribution: The clinic's Service Users' Research Advisory Group contributed to formulating the objective and design of the study. Results were presented at the clinic's annual PPI conference.